2013
DOI: 10.1128/jb.00718-13
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Analysis of Burkholderia pseudomallei Identifies Putative Novel Virulence Genes, Including a Microbial Regulator of Host Cell Autophagy

Abstract: e Burkholderia pseudomallei, the causative agent of melioidosis, contains a large pathogen genome (7.2 Mb) with ϳ2,000 genes of putative or unknown function. Interactions with potential hosts and environmental factors may induce rapid adaptations in these B. pseudomallei genes, which can be discerned through evolutionary analysis of multiple B. pseudomallei genomes. Here we show that several previously uncharacterized B. pseudomallei genes bearing genetic signatures of rapid adaptation (positive selection) can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…Yet another possible explanation for the low percentage of H. pylori-containing autophagosomes is that autophagy could be induced by H. pylori effector proteins to elicit the degradation of cellular components and release nutrients for use by the bacteria. For example, BPSS0180, a type VI cluster-associated gene of Burkholderia pseudomallei, induces canonical autophagy that does not target intracellular bacteria, but presumably targets host cell components leading to their degradation to smaller components that are usable by the bacteria [45].…”
Section: Discussionmentioning
confidence: 99%
“…Yet another possible explanation for the low percentage of H. pylori-containing autophagosomes is that autophagy could be induced by H. pylori effector proteins to elicit the degradation of cellular components and release nutrients for use by the bacteria. For example, BPSS0180, a type VI cluster-associated gene of Burkholderia pseudomallei, induces canonical autophagy that does not target intracellular bacteria, but presumably targets host cell components leading to their degradation to smaller components that are usable by the bacteria [45].…”
Section: Discussionmentioning
confidence: 99%
“…PlcN3 is a basic protein and deletion of plcN3 resulted in attenuation in a hamster model [77]. BPSL2198 is a phospholipase A2-like protein that when ectopically expressed in HeLa cells localized to the nuclear periphery and caused cell death [78]. Additionally, BPSL1549 or Burkholderia Lethal Factor 1 (BLF1), is a glutamine deamidase which destroys the RNA helicase ability of elongation factor 4A at the start of translation [79].…”
Section: Other Secreted Proteinsmentioning
confidence: 99%
“…BPSS0945, a putative exported peptidase, localized to the nucleus when expressed in HeLa cells and resulted in increased MNGC formation. This protein also contains a human microtubule-associated serine/threonine kinase-like (MASTL) domain; MASTL proteins aid in facilitation of mitosis, anaphase, and cytokinesis, which could implicate host cell growth and expansion as ideal conditions for MNGC formation [78]. The senescence marker LfpA (BPSS2074) was able to modify macrophages to resemble osteoclasts; these osteoclastic markers are also detected on MNGCs [93].…”
Section: Mngc Formationmentioning
confidence: 99%
“…Six proximal genes (BPSS0945; BPSS0948-281 BPSS0952) were also upregulated by 3.1-to 4.7-fold (9 to 26x; Table S1). One of these, 282 BPSS0945, is a peptidase and a putative virulence factor that may play a role in multinucleated 283 giant cell formation (Singh et al 2013). 284…”
Section: Several Regulators With Decreased Transcription In the Cf Ismentioning
confidence: 99%
“…shown that CPS-III expression is tied to that of CPS-I genes (Ooi et al 2013). and BPSS1683-BPSS1685.…”
Section: Environment 328mentioning
confidence: 99%